BIOMIMETIC SYNTHESIS, CHARACTERIZATION AND EVALUATION OF ANTIOXIDANT, ANTIMICROBIAL EFFICACY OF SILVER NANOPARTICLES USING ANDREDERA CORDIFOLIA LEAF EXTRACT - K, RAJATHI; S, Suja (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study is focussed on the biosynthesis of silver nanoparticles using aqueous extract of Andredera cordifolia and to investigate the free radical scavenging potential, antimicrobial activity of the nanoparticles against different human pathogens. Methods: The formation of silver nanoparticles was indicated by the colour change from colourless to reddish brown. Biosynthesized nanoparticles was characterised using several techniques, viz- UV-Vis spectroscopy, FT-IR, XRD, TEM, SEM and EDAX analysis. The free radical scavenging potential was measured by DPPH, FRAP assay, antimicrobial activity against six microorganisms was tested using disc diffusion method. Â Results: UV-Vis spectral analysis showed silver Surface Plasmon Resonance band at 426 nm. Â The crystalline morphology and size of the nanoparticles were determined by TEM, SEM, and X-ray diffraction studies which showed the average size of the nanoparticles in the range 40 â€“60nm. Â The biologically synthesized nanoparticles efficiently inhibited pathogenic organisms such as E. coli, Staphylococcus aureus, Klebsiella Pneumonia, Pseudomonas aeruginosa and Proteus vulgaris. Â The biosynthesized nanoparticles might serve as a potent antioxidant as revealed by DPPH assay and FRAP assay. Conclusion: The biosynthesis of silver nanoparticles had several advantages in pharmaceutical applications as well as large scale commercial production. Key Words: Silver nanoparticle, Andredera cordifolia leaf, SEM,TEM,XRD,antioxidant, antimicrobial,etc.